ANALISIS MODAL KERJA PT.TUNAS PRIMA SEJAHTERAH SAMARINDA - Tansil, Lisa (EKONOMIA, 2012)
Lisa Tansil , Working Capital Analysis PT . Tunas Prima Sejahterah samantha ( under the guidance of Mr. LCA . Robin Jonathan and Mrs. Elfreda A. Lau ) Management of working capital management regarding the company's current account ( current assets and current liabilities ) . Working capital management is one of the most important aspects of the overall management of corporate spending . If the company can not maintain